Collective Thomson scattering measurements of fast-ion transport due to sawtooth crashes in ASDEX Upgrade. (22nd July 2016) - Rasmussen, J.; Nielsen, S.K.; Stejner, M.; Galdon-Quiroga, J.; Garcia-Munoz, M.; Geiger, B.; Jacobsen, A.S.; Jaulmes, F.; Korsholm, S.B.; Lazanyi, N.; Leipold, F.; Ryter, F.; et al.
Abstract: Sawtooth instabilities can modify heating and current-drive profiles and potentially increase fast-ion losses. Understanding how sawteeth redistribute fast ions as a function of sawtooth parameters and of fast-ion energy and pitch is hence a subject of particular interest for future fusion devices. Here we present the first collective Thomson scattering (CTS) measurements of sawtooth-induced redistribution of fast ions at ASDEX Upgrade. These also represent the first localized fast-ion measurements on the high-field side of this device. The results indicate fast-ion losses in the phase-space measurement volume of about 50% across sawtooth crashes, in good agreement with values predicted with the Kadomtsev sawtooth model implemented in TRANSP and with the sawtooth model in the EBdyna_go code. In contrast to the case of sawteeth, we observe no fast-ion redistribution in the presence of fishbone modes. We highlight how CTS measurements can discriminate between different sawtooth models, in particular when aided by multi-diagnostic velocity-space tomography, and briefly discuss our results in light of existing measurements from other fast-ion diagnostics.